2009
DOI: 10.1523/jneurosci.5211-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Motor Unit Recruitment Strategies Are Altered during Deep-Tissue Pain

Abstract: Muscle pain is associated with decreased motor unit discharge rate during constant force contractions. As discharge rate is a determinant of force, other adaptations in strategy must explain force maintenance during pain. Our aim was to determine whether motor unit recruitment strategies are altered during pain to maintain force despite reduced discharge rate. Motor unit discharge behavior was recorded in two muscles, one with (quadriceps) and one without [flexor pollicis longus (FPL)] synergists. Motor units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
103
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 32 publications
12
103
1
Order By: Relevance
“…Moreover, recent studies using intra-muscular electromyography (EMG) recordings have shown that pain (induced in either muscular or non-muscular tissue) results in changes in the motorunit recruitment strategy, revealing that the effect of pain is not limited to a uniform inhibition of the motoneuron pool but, rather, includes more subtle changes in the distribution of output to the motoneuron pool. 20,21 However, it is still unclear whether these alterations in motor function observed at the muscular level reflect changes at the peripheral, spinal, or cortical level.…”
Section: Does Acute Pain Interfere With Motor-cortex Activity?mentioning
confidence: 99%
“…Moreover, recent studies using intra-muscular electromyography (EMG) recordings have shown that pain (induced in either muscular or non-muscular tissue) results in changes in the motorunit recruitment strategy, revealing that the effect of pain is not limited to a uniform inhibition of the motoneuron pool but, rather, includes more subtle changes in the distribution of output to the motoneuron pool. 20,21 However, it is still unclear whether these alterations in motor function observed at the muscular level reflect changes at the peripheral, spinal, or cortical level.…”
Section: Does Acute Pain Interfere With Motor-cortex Activity?mentioning
confidence: 99%
“…) or as de-recruitment of motor units (Hug et al 2013;Minami et al 2013;Tucker et al 2009) for the painful muscle. In such cases, maintenance of the net motor output (e.g., a similar movement/position) is achieved by redistribution of the activity to other motoneurons or to other muscles (Hug et al 2013(Hug et al , 2014Minami et al 2013;Tucker et al 2009).…”
mentioning
confidence: 99%
“…It has recently been demonstrated that patients with knee OA who have quadriceps activation failure acquire greater volitional quadriceps activation and muscle strength gain from an intervention aimed at blocking pain sensation centrally in combination with exercise (49). Second, the average pain intensity was 16.2 mm, which is lower than that reported in previous studies (25)(26)(27)36). The time course of experimental IPFP pain shows that maximum pain intensity is reached within 5 minutes, and then gradually declines over the following 10 -12 minutes (23).…”
Section: Discussionmentioning
confidence: 76%
“…Second, the "pain adaptation" theory hypothesizes that pain inhibits agonistic muscles and facilitates antagonistic muscle activity (35). Excitation of group III and IV afferents can reduce muscle force, electromyographic activity, and discharge rate of some motor units (14,17,25,27,36), and reduce quadriceps activation. Our data do not support this hypothesis, as uniform inhibition of the quadriceps in the pain group would be expected to reduce the training volume and a parallel lower strength gain over time compared to the control group, but no differences in training volume and a larger strength gain were found in the pain group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation